Allogeneic CD34‐selected stem cell boost as salvage treatment of life‐threatening infection and severe cytopenias after CAR‐T cell therapy. Issue 10 (20th August 2022) - de Tena, Pablo Silva; Bailén, Rebeca; Oarbeascoa, Gillen; Gómez‐Centurión, Ignacio; Pérez‐Corral, Ana; Carbonell, Diego; Martínez‐Laperche, Carolina; Sancho, Milagros; Bastos‐Oreiro, Mariana; Conde‐Royo, Diego; Fernández‐Caldas, Paula; Muñoz, Cristina; et al.
Abstract: Background: A variable incidence of profound cytopenia has been described in patients receiving chimeric antigen receptor T‐cell (CAR‐T) therapy for relapsed or refractory (R/R) B‐cell acute lymphoblastic leukemia (ALL). This complication leads to severe infection in some cases, especially those who present additional risk factors including prior hematopoietic stem cell transplantation (HSCT). Study Design and Methods: We report a case of breakthrough invasive fungal infection in a patient with prolonged neutropenia after CAR‐T cell therapy administered for relapsed B‐cell ALL after allogeneic haploidentical HSCT. Results: After disease progression was discarded, therapy with antifungal agents, G‐CSF and thrombopoietin analogue was started. However, no sign of haematological recovery or infection improvement was observed. A fresh mobilized selected CD34‐stem cell boost from her haploidentical transplant donor was infused without further conditioning. Within 15 days of mobilized CD34‐boost administration the patient showed complete resolution of both the aplasia and fungal infection. Discussion: This case illustrates as proof‐of‐concept the efficacy and safety of selected CD34‐stem cell boost from prior donor as salvage treatment of prolonged cytopenias after CAR‐T cell therapy.